Variant spectrum of F8 and F9 in hemophilia patients from southern China and 26 novel variants - Li, Fucheng; He, Liya; Chen, Guilan; Lu, Yan; Li, Ru; Zhang, Yongling; Jing, Xiangyi; Ling, Rujuan; Li, Dongzhi; Liao, Can (Frontiers in Genetics, 2023)
Hemophilia, an X-linked recessive disorder, is characterized by spontaneous or trauma-induced prolonged bleeding. It is classified as hemophilia A when caused by variants in the F8 gene, and hemophilia B when caused by F9 variants. Few studies have described hemophilia variants in the Chinese population. This study aimed to investigate the clinical and genetic profiles of 193 hemophilia patients from southern China. Utilizing Sanger sequencing, multiplex ligation-dependent probe amplification, gap detection, long-range PCR, and multiplex PCR, we identified both F8 and F9 gene variants. Pregnant women with a history of hemophilia A offspring underwent amniocentesis or villus sampling for the variant detection. Variants in F8 and F9 were pinpointed in 183 patients, with 26 being novel discoveries. Notably, genetic testing was absent in the initial evaluation of 133 out of 161 patients, leading to a protracted average definitive diagnosis timeline of two years. Remarkably, two hemophilia A cases with anticipated severe phenotypes due to protein-truncating variants presented with only moderate or mild clinical manifestations. Among the 40 fetuses tested, 34 were males, with 17 exhibiting hemizygous variants in the F8 gene. Our results contribute to the broader understanding of F8 and F9 variant spectrum and highlight the underuse of genetic analyses in southern China.